Husband’s Knowledge Level about the Importance of Husband’s Role and Support to Wife during Pregnancy, Childbirth and Postpartum Period - Marlynda Happy Nurmalita Sari; Sopie Ramadanti (Prodi DIII Kebidanan Blora Poltekkes Kemenkes Semarang, 2021)
Husband's attention is the most basic level of a woman's needs in pregnancy, childbirth and postpartum. The presence of a husband to accompany his wife during childbirth is highly expected because it can provide support to his wife, so that her wife feels safe, comfortable and patient so that pregnancy, birth and post partum will run smoothly and normally. The presence of the husband will bring closer family relationships to obtain emotional support so that it will reduce medical intervention. This study aims to determine the husband's level of knowledge about the importance of his role and support for his wife during pregnancy, childbirth and the puerperium both from predisposing factors, supporting factors and driving factors in Kampung Desa RT 003 RW 01 Duren Mekar. This research is descriptive with a cross sectional design and the type of data taken is primary data using a questionnaire, then the results are processed by the stages of data selection, data tabulation, and percentage calculations which are then presented in a frequency distribution table. While the respondents taken are men from fertile age couples who already have children who live in the Kampung Desa environment RT 003 RW 01 Duren Mekar with a sample of 34 respondents from a total population of 52 respondents. From the results of the study, it was found that 32 respondents (94.1%) had a good level of knowledge, as many as 28 respondents (100%) of 28 respondents with a high level of education had a good level of knowledge, as many as 27 respondents (93.1%) from 29 respondents who received information from health workers had a good level of knowledge, as many as 32 respondents (94.1%) of the 34 respondents who had a working status when their wives were pregnant until postpartum had a good level of knowledge, as many as 16 respondents (94.1%) ) of 17 respondents who fall into the category of late adulthood (36-45 years) have a good level of knowledge. It is hoped that further research will allow researchers to examine more and more extensive other variables that affect the husband's level of knowledge about the importance of his role and support for his wife during pregnancy until postpartum Key word: Knowledge, Education, Sources of Information, Occupation, Age